Defective PITRM1 mitochondrial peptidase is associated with Aβ amyloidotic neurodegeneration. Issue 3 (23rd December 2015) - Brunetti, Dario; Torsvik, Janniche; Dallabona, Cristina; Teixeira, Pedro; Sztromwasser, Pawel; Fernandez‐Vizarra, Erika; Cerutti, Raffaele; Reyes, Aurelio; Preziuso, Carmela; D'Amati, Giulia; Baruffini, Enrico; Goffrini, Paola; et al.
Abstract: Mitochondrial dysfunction and altered proteostasis are central features of neurodegenerative diseases. The pitrilysin metallopeptidase 1 (PITRM1) is a mitochondrial matrix enzyme, which digests oligopeptides, including the mitochondrial targeting sequences that are cleaved from proteins imported across the inner mitochondrial membrane and the mitochondrial fraction of amyloid beta (Aβ). We identified two siblings carrying a homozygous PITRM1 missense mutation (c.548G>A, p.Arg183Gln) associated with an autosomal recessive, slowly progressive syndrome characterised by mental retardation, spinocerebellar ataxia, cognitive decline and psychosis. The pathogenicity of the mutation was tested in vitro, in mutant fibroblasts and skeletal muscle, and in a yeast model. A Pitrm1 +/− heterozygous mouse showed progressive ataxia associated with brain degenerative lesions, including accumulation of Aβ‐positive amyloid deposits. Our results show that PITRM1 is responsible for significant Aβ degradation and that impairment of its activity results in Aβ accumulation, thus providing a mechanistic demonstration of the mitochondrial involvement in amyloidotic neurodegeneration. Synopsis: A clinically peculiar neurodegenerative disorder in humans was indentified and shown to be caused by a pathogenic homozygous mutation in PITRM1, encoding an oligopeptidase of the mitochondrial inner compartment. The neuropathology of a PITRM1 −/+ mouse provides genetic evidence that Aβ is present within mitochondria, and demonstrates a link between impaired PITRM1 activity and Aβ amyloidotic neurodegeneration in mammals. A homozygous disease segregating missense mutation was found in the PITRM1 gene in two siblings of a consanguineous family. The pathogenic role of the mutation, causing PITRM1 instability, was validated by in vitro assay, characterization of mutant fibroblasts from patients and in PITRM1 knocked‐down human fibroblasts, and in a mutant yeast model. A hemizygous PITRM1 knockout mouse displayed reduced amount of PITRM1, associated with slowly progressive neurodegeneration, hallmarked by accumulation of Aβ amyloid in the brain. Abstract : A clinically peculiar neurodegenerative disorder in humans was indentified and shown to be caused by a pathogenic homozygous mutation in PITRM1, encoding an oligopeptidase of the mitochondrial inner compartment. The neuropathology of a PITRM1 −/+ mouse provides genetic evidence that Aβ is present within mitochondria, and demonstrates a link between impaired PITRM1 activity and Aβ amyloidotic neurodegeneration in mammals.